Analysis of the Role of Local Government in Empowering Local Papuan Msmes in Sorong City - Tumoka, Isgar Muhammad Ricky; Rumakat, Laila Qadriyah; Rahangiar, Wensislaus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Indigenous Papuans (OAPs) have an important role in cultural and economic diversity in the Unitary State of Indonesia, especially in Southwest Papua Province which is a newly formed province. The empowerment of local Papuan MSMEs is a form of maintaining cultural sustainability and providing economic opportunities to the indigenous Papuan people. The local government of Sorong city has a great responsibility in supporting the development of MSMEs of indigenous Papuans so that they are able to compete in the local market. The urgency in this study is to identify policy recommendations to increase the empowerment of local Papuan MSMEs, reduce economic disparities, and increase the economic independence of indigenous Papuans. The purposeof this study is to analyze (1) The role of local governments in the empowerment of local Papuan Micro, Small and Medium Enterprises (MSMEs) in the city of Sorong, (2) The supporting and inhibiting factors in the empowerment of local Papuan MSMEs in the city of Sorong, (3) The proposed policy recommendations to improve the empowerment of local Papuan MSMEs in the city of Sorong that are effective and sustainable. The research method used in this study is qualitative, data collection techniques are carried out through observation, interviews, documentation, and focus group discussions. The results of the study show that the Sorong City Regional Government, in this case the Cooperatives and MSMEs Office, has a strategic role in the development of local MSMEs in Sorong City, which is carried out through two functions, namely as a facilitator and as a catalyst.